2024
DOI: 10.1108/ijwbr-07-2023-0042
|View full text |Cite
|
Sign up to set email alerts
|

Hold my beer! Consumer perceptions of innovative and sustainable secondary packaging

Cortney L. Norris,
Marissa Orlowski,
Scott Taylor, Jr.

Abstract: Purpose As a result of both shifting social concerns and stricter legislation, many companies are seeking innovative and sustainable solutions for both primary and secondary packaging. The craft beer industry has made the most notable advancements with a variety of alternatives to the traditional secondary packaging (e.g. plastic rings) used to link beer cans. Yet, despite the impact packaging has on consumer purchase behavior and the environment, secondary packaging has received far less attention in the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…For environmentally conscious consumers, knowing how and why packaging is sustainable is a key issue in purchasing decision-making. As noted by Norris et al (2023), 80% of food and drink purchasing decisions occur at the point of sale, meaning that most sales happen without a product being sampled. Therefore, the design of packaging is the key element in distinguishing products.…”
Section: Beer Mementioning
confidence: 99%
See 4 more Smart Citations
“…For environmentally conscious consumers, knowing how and why packaging is sustainable is a key issue in purchasing decision-making. As noted by Norris et al (2023), 80% of food and drink purchasing decisions occur at the point of sale, meaning that most sales happen without a product being sampled. Therefore, the design of packaging is the key element in distinguishing products.…”
Section: Beer Mementioning
confidence: 99%
“…For smaller breweries, any changes have to be made carefully and with the full understanding of what such a resource investment means for other elements of the production cycle. The research of Norris et al (2023) has demonstrated that the choice of secondary packaging has no impact on the consumers' choice to purchase. This means that whatever choice is made, there will be a negligible difference in terms of sales.…”
Section: Beer Mementioning
confidence: 99%
See 3 more Smart Citations